Cancer Perceptions Among Smokeless Tobacco Users: A Qualitative Study of US Firefighters - Nattinee Jitnarin; Walker S.C. Poston; Sara A. Jahnke; Christopher K. Haddock; Hannah N. Kelley (Elsevier, 2020)
Background: Prevalence rates of smokeless tobacco (SLT) use among firefighters are remarkably high and substantially higher than similar occupational groups and the general U.S. population. The purpose of this study was to explore the perspectives of fire service personnel regarding cancer and its associations with tobacco and SLT use. Methods: This descriptive study used a qualitative approach. Key informant interviews were conducted in 39 career firefighters and fire service administration from across the U.S. Discussion were recorded, transcribed verbatim and transferred to NVivo software for narrative analysis. Topics explored included cancer perceptions, attitudes and beliefs, and cultural factors related to SLT use behaviors. Results: Major themes that emerged among fire service personnel included concerns about cancer and its risk factors including firefighting tasks, such as fire overhaul operations, and from their lifestyle behaviors, such as alcohol and tobacco use. Firefighters also suggested a number of reasons for their increased SLT use, such as fire department tobacco-free policy and fire service culture. Conclusion: The current study provides a rich foundation for future research, prevention, and intervention efforts for the fire service and research communities regarding tobacco and SLT use and cancer risk. Additional research on firefighters' cancer beliefs deserves future research in order to improve messaging about the risks of cancer due to firefighting.